Avaliação da expressão de integrina alfa2, proteína de choque térmico 47, e mediadores pro-inflamatórios e imunorregulatórios em resposta à infecção endodôntica - Wilson Bambirra Júnior (2014)
Aim: To examine alpha 2 integrin, molecular mediators, cytokines, and chemokines from cells in periapical interstitial fluid from root canal infections. Methodology: Subjects included 13 patients referred to the College of Dentistry at the Universidade Federal de Minas Gerais (Belo Horizonte, MG, Brazil). Clinical samples were taken from teeth with pulp necrosis and no patients had acute periapical symptoms at the time of the appointments. After cleaning and drying, 3 paper points were introduced into the root canal, passing passively through the root apex (2 mm) into the periapical tissues for 1 minute. The samples were collected immediately after root canal cleaning and 7days later (restrained root canal bacterial load) to characterize ITGA2, Hsp47, FAK, OPN, IL-1, TGF-,IL-17A , IL-10, IFN-, IL-8, CCL2/MCP-1, CCL5 gene expressions using Real Time PCR. Results: Significantly lower levels of TNF-, CCL5, CCL2/MCP-1, and IL-8 in teeth with restrained bacterial loads (second collection) compared to the first collection were observed. Similarly, the mRNA expression of the proteins SSP1/OPN and FAK decreased in samples from the second collection. The regulatory cytokine IL-10 mRNA was significant higher in the samples from the second collection compared to the first collection. mRNA expression of IL-1, IL-17A, IFN-, ITGA2 and Hsp47/SERPINH1 were similar at both time points. Conclusion: These findings suggest that after reducing the root canal bacterial load an anti-inflammatory response take place in periapical area regulated by the Treg IL-10 cytokine.